Effect of Vanillic Acid in Streptozotocin Induced Diabetic Neuropathy - Khairnar, Shubham; Pawar, Shubhangi; Patil, Vinod; Rudrapal, Mithun (Asian Journal of Biological and Life Sciences, 2020)
Diabetic neuropathy is a one of the usual complications of both type 1 and 2 diabetes mellitus. Lesion to or diseases of somatosensory system may lead to neuropathic pain which are severally painful. Apart from other etiological factors, the oxidative stress has vital role in the pathogenesis and continuation of diabetic neuropathy. Vanillic acid is the phenolic compound and aromatic secondary plant metabolite. Phenolic acids are proved to have antioxidant and neuroprotective role. So, this study was undertaken to evaluate the effects of vanillic acid on STZ induced diabetic neuropathy by assessing behavioural, biochemical, electrophysiological and histological changes. Diabetes was induced in Wistar rats by using single injection of STZ (55 mg/kg, i.p.). After confirmation of diabetes (blood glucose level >200mg/dl), animals treated with Gabapentin (300 mg/kg, p.o.) and Vanillic acid (25, 50 and 100 mg/kg, p.o) for next 4 weeks. Vanillic acid (50 and 100 mg/kg) treated rats showed significant (p<0.05) behavioral changes, decrease in blood glucose levels, significant (p<0.05) increase in reduced glutathione (RGSH) level. Treatment with vanillic acid has also reversed histopathological and electrophysiological changes. In conclusion, the present study suggested anti-hyperglycemic, antioxidant and neuroprotective effect of vanillic acid in diabetic neuropathy.
Keywords: Allodynia; Antioxidants; Diabetes; Hyperalgesia; Hyperglycemia; Vanillic acid